(3HZjI GdWGdH hOdjd GdQGZHs - (3CHh YHO Gddg eMeO Hf MeGO GdCfOdSjs; (3GdbGVj YjGV , YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HSW GdfYeI , hCbGe GdMLI GdN s
(3BNQgG (B:s
(3GfJgi Pdc HMeO Gddg hMSf Yhfg , hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hSde s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs